Characterising the sleep-wake behaviour of adolescents in a sample of South African high school students in Makhanda, Eastern Cape - Mandondo, Nathasha Luleka (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Sleep plays a significant role during adolescence. Overall, sleep is essential for growth and development, cognitive function, memory consolidation, concentration, alertness, mental and physical health, as well as the overall quality of life. During adolescence though, sleep-wake behaviour has been shown to undergo drastic changes, progressing from the early ages of 11-13 years through to late adolescence while attending school. During this period, adolescents experience later bedtimes, earlier waketimes, and less than recommended sleep durations, especially on weekdays during the school term. On weekends, however, adolescents tend to further delay their bed and wake times, resulting in discrepancies between week-and-weekend sleep-wake behavior. These changes are driven by a variety of systemic factors, that include biological, psychosocial, school, and behavioural changes that adolescents experience. The interaction of systematic factors has been described as the "Perfect Storm of insufficient and inappropriately-timed sleep" (Carskadon, 2011a; Crowley et al., 2018). While previous research on adolescent sleep has been focused mainly in countries of the Global North, there has been comparatively less research in the Global South, particularly in countries like South Africa, and in out of large city centres like Johannesburg and Cape Town. It is also not known what the impact of certain demographic factors, such as learner sex, boarding/day schooling, and public/private schooling is on sleep-wake habits. Therefore, the purpose of this study was to explore the sleep-wake behaviour of a sample of late adolescents from public and private schools in Makhanda in the Eastern Cape of South Africa and to make comparisons between different groups within. Method: This study is comprised of two phases. Phase one adopted a cross-sectional design to characterise Grade 12 learners' (final year students) sleep-wake behaviour across various public and private schools. This was achieved through the administration of an amended version of the School Sleep Habits Survey (SSHS). The SSHS included questions that capture demographic information, academic performance, sleep duration at different times of the week and also incorporated scales to assess daytime sleepiness, sleep-wake behavior problems, depressive mood, and chronotype. Phase two adopted an observational descriptive design. The sleep-wake behaviour of a sample of Grade 11 learners was tracked for 9 days using the Core Consensus Sleep Diary and Actigraphy. Data were not normally distributed and were thus analysed using non-parametric statistics and all data were displayed as the median and interquartile range (no 1-3). Results: Analysed surveys totalled 231. All participants were Grade 12s (final year of high school), aged between 17-19, from three private schools (n=152) and two public schools (n=79). The sample consisted of students identifying as females (n=94) and males (n=137). Participants self-identified as either Black/African (n=73), White (n=125), Colored (n=32) and as Indian (n=1). Over half of the sample lived in boarding houses/hostels (n=130) and slightly less than half (n=95) were day scholars. For Phase One, the median obtained for self-reported sleep duration on weekdays was 07hrs (06hrs-07hrs:18min) and 08hrs (07hrs-09hrs) on the weekend (p<0.01; z=10). The median for self-reported bedtime on weeknights was 11:00 (10:30-11:30) p.m., while on the weekends, it was an hour later i.e., 12:00 a.m. (11:00 p.m. -12:37 a.m.; p<0.01; z=9.4). Self-reported waketime on weekdays was 06:20 (06:00-06:30) a.m. and it was one-hour forty minutes later on weekends i.e., 08:00 (07:00-09:00) a.m. (p<0.01; z=13). With regards to sex differences on school mornings, females reported waking up 14 minutes later than their male counterparts (p<0.01; z=-3.1). On school mornings, day scholars reported significantly earlier waketimes than boarders (p<0.01; z=8.1). The opposite was found on weekends with day scholars reporting significantly later waketimes than boarders (p<0.01; z=-4.1) while day scholars reported going to bed significantly later than boarders during weekends (p<0.01; z=-2.7). There were noteworthy differences between types of schools with public school learners reporting earlier bed (p<0.01; z=3.9) and wake times (p<0.01; z=10) than private school learners on weekdays. On the weekend, however, public school learners reporting later bed (p=0.01; z=-2.7) and wake times (p<0.01; z=-4.4) than private school learners. Overall, the Grade 12 learners scored 12 (11-15) on the depressed mood scale indicating a trend towards high self-reported depressive symptoms, and 26 (23-30) on the ME scale, which demonstrated that this sample population reflects a preference for neither evenings nor mornings. The majority (75 %; n=174) of the Grade12 learners perceived themselves as getting too little sleep, 59% (n=134) reported waking up at least once during the night and 92% (n=213) reported experiencing varying degrees of daytime sleepiness. There was a relationship between caffeine consumption and usage of electronic devices (EDs) before bedtime and some sleep parameters. Specifically, the frequency of consumption of coffee/tea and soda had a medium and positive correlation with sleep onset latency as well as to the scale of sleep-wake problems. Academic performance was also positively and significantly correlated with self-reported mean weekday waketime and negatively correlated with mean weekend sleep duration as well as Weekend Waketime Delay (WWD). For Phase Two, the median self-reported sleep duration for 14 female boarders recorded in sleep diaries i.e.,07:32 (07:22-07:55) and the total sleep time (TST) recorded by the actigraphy i.e., 07:06 (06:54-07:35) and was less than the recommended sleep duration of 8-10 hours for adolescents and not significantly different (p=0.18; z=1.3). However, median sleep duration on the weekend was significantly longer on both actigraphs (08:16; 07:22-08:40) and sleep diaries (08:24; 07:59-08:51) and not significantly different (p=0.3; z=1.1). Overall, bedtimes, waketimes, and sleep onset latency, for both weekdays and weekends, did not differ significantly between the sleep diary responses and actigraph recordings. Discussion: Adolescents in this cohort, like many around the world report weekday sleep durations that are shorter than the recommended 8-10 hours. This may probably partly be explained by later bedtimes influenced by academic obligations, bedtime autonomy, and screen time as well as early waketimes influenced by school start times as indicated in the reasons given for bedtimes. Insufficient sleep during school nights, in this cohort, likely resulted in an accumulated sleep debt which may explain the extended sleep duration and later waketimes on weekends. Weekday waketimes were probably determined by commuting and school-related demands, specifically, school start times as indicated in the reasons given for waketimes. Thus, the results of this study do, in part, align with the factors outlined in the Perfect Storm model of poorly timed and insufficient sleep in adolescents proposed by Carskadon (2011a). Personal characteristics or contextual factors, such as being a boarder or a day scholar, attending a public or private school as well sex differences, accompanied by lifestyle factors such as the consumption of caffeine and usage of electrical devices may have interacted and influenced bed and wake times, resulting in what has been termed "a Perfect Storm of insufficient and inappropriately-timed sleep" in this cohort. Conclusion: The current study provided new insight into the sleep-wake behaviour of late adolescents in Makhanda, Eastern Cape of South Africa. More research is encouraged in the South African context. This knowledge can be used to implement contextually appropriate sleep hygiene education programs in the school curriculum and on an individual level. Furthermore, the results point to the fact that early school start times, in concert with other lifestyle and personal factors may be contributing to insufficient sleep in this group. These results, therefore, highlight the need for schools in this context to consider interventions such as delaying school start times to possibly improve sleep in this context.,Thesis (MSc) -- Faculty of Science, Human Kinetics and Ergonomics, 2021
Keywords: Sleep-wake cycle -- South Africa -- Makhanda; Sleep deprivation -- South Africa -- Makhanda; Academic achievement -- South Africa -- Makhanda; Mood (Psychology) -- South Africa -- Makhanda; High school students Conduct of life; Teenagers Health and hygiene -- South Africa -- Makhanda; Teenagers Sleep -- South Africa -- Makhanda; Depression in adolescence -- South Africa -- Makhanda